Testing the motor proficiency barrier hypothesis for physical activity and weight status in youth - Lopes, Vitor P. (2021)
The purpose was to evaluate the implications of a proficiency barrier (PB) for physical activity (PA), sedentary time (ST) and weight status (WS) in a two-stage study. In Stage 1, motor quotient (MQ) cut-off values, based on the KTK test, for differentiating overweight/obese from normal weight, and sedentary from non-sedentary were identified in a sample of 734 children (353 girls) of 10 years of age. In Stage 2, the cut-off values were used to define low and high (respectively below and above the PB) MQ groups among 217 youth (118 girls) of 12.9(0.4) years of age. WS, PA and ST in the two MQ groups were compared at baseline and 1.5 years later. Chi-square tests were used to test the independence of low and high MQ classification on MS, moderate-to-vigorous PA, and sedentary time. Odds of being overweight/obese and sedentary according to MQ status at baseline were calculated. MQ of 79 for girls and 75 for boys were defined as the PB. In girls, the PB predicted significantly different classifications of WS, and a combination of WS and moderate-to-vigorous PA. In boys, the PB predicted significantly different classifications based on combined WS and moderate-to-vigorous PA at baseline. Having a MQ below the PB was associated with a 2.78 higher probability of being overweight/obese. In conclusion, the results suggest that a PB that influences PA and WS among youth may exist.